Booms, bubbles, and busts in US stock markets - Western, David L. (Routledge, 2004)
Examines the current conditions before looking back to the events of the last century - The Great Depression, the 1970s oil crisis, the party-for-the-rich atmosphere of the 1980's and the emergence of the new economy.